Efek Perubahan Dosis Radiasi Dan Kualitas Gambar Pada Hasil Radiograph Dengan Luas Kolimasi Berbeda - Surdiyah Asriningrum (Jurnal Imejing Diagnostik (JImeD), 2020)
Background: The use of variations of collimation will provide a low dose to the patient and radiographic results that provide a good quality image. This research is to examine the effects of various collimation sizes on the image quality and radiation doses when using x-ray machine at Radiology laboratory of  Al-Islam Polytechnic, Bandung. How much the change in density values that occur and to find out of scattering radiation received by the patient in the Radiology laboratory of  Al-Islam Polytechnic, Bandung.Methods: This type of research is an experimental study with participatory observation data collection. at the Radiology Laboratory of the Al-Islam Polytechnic, Bandung The independent variable is variations of collimation, the dependent variables are quality image and doses radiation. Data collection was carried out by exposing a Stepwedge stored on a 35 x 35 cm radiographic cassette with different irradiation areas and pendose as a measure of radiation. Radiograph results were analyzed by a densitometer. Then the results will be analyzed using digraph to know the movement of each different irradiation field area.Results: The results showed that there were influences of changes in the variation of collimation.  Density value and scattered radiation of each different irradiation field area produces are different values. The smaller area of the irradiation field. Is, the higher density value and low dose. Thus, to get the best density value and the low dose is required to reduce the width of the collimation field conducted.Conclusions: There was an influence variation of collimation on the quality of the image and dose to the patient.